Neuroglobin and friends. Issue 12 (14th July 2017) - Fiocchetti, Marco; Cipolletti, Manuela; Brandi, Valentina; Polticelli, Fabio; Ascenzi, Paolo
Abstract: In the year 2000, the third member of the globin family was discovered in human and mouse brain and named neuroglobin (Ngb). Neuroglobin overexpression significantly protects both heart and brain from hypoxic/ischemic and oxidative stress‐related insults, whereas decreased Ngb levels lead to an exacerbation of tissue injuries. Moreover, Ngb overexpression protects neurons from mitochondrial dysfunctions and neurodegenerative disorders such as Alzheimer disease; however, it facilitates the survival of cancer cells. Neuroglobin, representing a switch point for cell death and survival, has been reported to recognize a number of proteins involved in several metabolic pathways including ionic homeostasis maintenance, energy metabolism, mitochondrial function, and cell signaling. Here, the recognition properties of Ngb are reviewed to highlight its roles in health and disease. Abstract : In the year 2000, the third member of the globin family was discovered in human and mouse brain and named neuroglobin. Neuroglobin overexpression significantly protects the heart and brain from hypoxic/ischemic and oxidative stress–related insults, neurons from mitochondrial dysfunctions, and neurodegenerative disorders such as Alzheimer disease; however, it facilitates the survival of cancer cells. Neuroglobin has been reported to recognize a number of proteins involved in several metabolic pathways including ionic homeostasis maintenance, energy metabolism, mitochondrial function, and cell signaling.